Morphological and functional alterations of human spermatozoa after incubation with two organophosphorus insecticides - Dayananda, Pavithra D.; Peiris, D.C. (Wulfenia Journal, 2016)
Attached
Keywords: admire; lebaycid; male fertility; reproductive toxicity